Optimization Of Phenolic Content From Tulsi Plant (Ocimum Sanctum) By Ultrasonic-Assisted Extraction: Comparison With Conventional Soxhlet Extraction Method - Rahimah, Abd Rahim (2012)
This study is mainly about optimization of the extraction of phenolic compound from one kind of valuable herbs which is Tulsi plant (Ocimum Tenuiflorum) by comparing between ultrasonic assisted and conventional Soxhlet methods. Tulsi plants have variety of function which made it demanding in market due to the application and function of this type of herbs. Thus, this research was conducted as to investigate the total phenolic compound in ethanolic extract of the Tulsi plant leaves by verifying different parameters. The parameters that are considered for this study are the differences size particle of leaves, extraction time, temperature, and volume of ethanol solvent. The total phenolic compound in terms of concentration and mass Gallic acid equivalents was determined using HPLC. From the observation, sonication of ultrasonic assisted extraction method could improve the yield of phenolic compound and shortened the extraction times. Besides, it also can decrease the organic solvent consumption thus may lead to the increasing of pollution prevention. As a conclusion, ultrasonic extraction is one of the potential alternative methods comparing than conventional Soxhlet method.